3D Bioprinting Technology: Scientific Aspects and Ethical Issues. - Patuzzo, Sara; Goracci, Giada; Gasperini, Luca; Ciliberti, Rosagemma (Science & Engineering Ethics, 2018)
The scientific development of 3D bioprinting is rapidly advancing. This innovative technology involves many ethical and regulatory issues, including theoretical, source, transplantation and enhancement, animal welfare, economic, safety and information arguments. 3D bioprinting technology requires an adequate bioethical debate in order to develop regulations in the interest both of public health and the development of research. This paper aims to initiate and promote ethical debate. The authors examine scientific aspects of 3D bioprinting technology and explore related ethical issues, with special regard to the protection of individual rights and transparency of research. In common with all new biotechnologies, 3D bioprinting technology involves both opportunities and risks. Consequently, several scientific and ethical issues need to be addressed. A bioethical debate should be carefully increased through a multidisciplinary approach among experts and also among the public.